Konsep Hukum Islam Dalam Penanggulangan Konflik dan Bentrok Fisik di Indonesia - A, Abriansyah; R, Abdurrahman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Indonesia, a nation with a Muslim-majority population, holds significant potential for implementing Islamic legal concepts in handling conflicts and physical clashes. These concepts, such as tabayyun (verification), tahkim (arbitration), musyawarah (deliberation), islah (reconciliation), and amar ma’ruf nahi munkar (enjoining good and forbidding wrong), offer a comprehensive and value-based approach. This paper aims to analyze these Islamic legal concepts in depth and explore their application within Indonesia’s diverse social context. The analysis will draw upon primary Islamic sources like the Quran and Hadith, alongside secondary literature from Islamic scholars and legal experts.This research aims to:Analyze the concepts of Islamic law in dealing with conflicts and physical clashes in Indonesia.Develop a framework for applying these Islamic law concepts in the context of Indonesia’s pluralistic society.